Investor Behaviour Analysis: The Impact Financial Performance, FOMO and Financial Literacy on Generation Z Investment Decisions - Wilamsari, Feni; Ana, Selvia Roos; Musriati, Titik (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
Investing is important for long-term financial planning for Gen Z, who have quick access to investment instruments such as stocks, bonds, and cryptocurrencies, yet many do not fully understand its role in building wealth. This study aims to examine the effect of company financial performance and the FOMO (Fear of Missing Out) phenomenon on Gen Z's investment decisions, as well as the role of financial literacy in moderating these two factors. Questionnaires were sent in order to gather research data, and a purposive sampling strategy was used to choose the sample. To investigate the moderating impact inside the model, the data were subjected to Moderated Regression Analysis (MRA) using EViews 13. The results showed that the company's financial performance did not have a significant effect on Gen Z's investment decisions. In contrast, FOMO shows a significant influence on Gen-Z investment decisions. In addition, this study also tested the moderating effect of financial literacy. The results show that financial literacy does not moderate the effect of corporate financial performance or FOMO on Gen Z investment decisions.